2021
DOI: 10.1891/crnr-d-20-00095
|View full text |Cite
|
Sign up to set email alerts
|

Flipping the Classroom: Incorporating Video Production in Public Health Nursing Education

Abstract: A video production activity utilizing a flipped-classroom approach was used in a public health nursing course to educate undergraduate nursing students about infectious diseases. After reviewing an audio-recorded lecture at home, students were divided into small groups to create short video clips on selected infectious diseases. Four themes emerged from the subsequent participant survey: engagement, in-depth understanding but concerns for new knowledge acquisition, practical, and room for improvement. The flip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A Korean study [34] found that students who watched a video of their own catheterization insertion and self-assessed it had higher communication (P < 0.01) and career competence (P < 0.01) compared to a control group of students who received only a bibliographic assessment guide. Grouping students to learn about infectious diseases using a "flipped classroom + short video" method can significantly improve students' communication and teamwork skills [35] . Surintorn et al [36] conducted a quasi-experimental study using a pretest-post-test design with 126 nurses in Thailand, in which nurses watched an online smoking cessation video.…”
Section: Improvement Of Communication and Career Awarenessmentioning
confidence: 99%
“…A Korean study [34] found that students who watched a video of their own catheterization insertion and self-assessed it had higher communication (P < 0.01) and career competence (P < 0.01) compared to a control group of students who received only a bibliographic assessment guide. Grouping students to learn about infectious diseases using a "flipped classroom + short video" method can significantly improve students' communication and teamwork skills [35] . Surintorn et al [36] conducted a quasi-experimental study using a pretest-post-test design with 126 nurses in Thailand, in which nurses watched an online smoking cessation video.…”
Section: Improvement Of Communication and Career Awarenessmentioning
confidence: 99%
“…TeamSTEPPS emphasizes training on communication and teamwork skills which can impact each of the aims for improving population health outcomes. Other teaching-learning strategies identified in the literature and on the Association of Community Health Nursing Educators (ACHNE)website include digital stories (LeBlanc, 2017), poster presentations(Rohlik & Krumwiede, 2020), case studies, and e-Learning modules(Eardley et al, 2018), video production(Kwon et al, 2021), role play, simulations(Aslan, 2020), videos, games, clickers, debates, photo journals, tabletop exercises, book discussions, and service-learning experiences (Association of Community Health Nursing Educators, 2022). [Correction added on 21 February 2023, after first online publication: In the preceding sentence, '(Association of Community Health Nursing Education, 2022)' has been corrected to '(Association of Community Health Nursing Educators, 2022)' in this version.]…”
mentioning
confidence: 99%